Time, memory, institution : Merleau-Ponty's new ontology of self - Morris, David, 1967- (Series in Continental thought., 2015)
"The rich and impressive essays in Time, Memory, Institution make a new and significant contribution to the field, dealing with works of Merleau-Ponty's that have only recently become available in English."